Efficient method for the synthesis of quinoxaline derivatives catalyzed by titanium silicate-1 - Chandrachood, Pranav S.; Jadhav, Amol R.; Garud, Dinesh R.; Deshpande, Nirmala R.; Puranik, Vedavati G.; Kashalkar, Rajashree V. (Research on Chemical Intermediates, 2020)
A series of quinoxaline derivatives were efficiently synthesized by convenient and simple procedure in excellent yields using 1 wt.% of titanium silicate (TS-1) catalyzed reaction of 1,2-diamines and 1,2-diketones in methanol at room temperature. This reaction is scalable to multigram scale and the catalyst is recyclable. [GRAPHICS] .
Keywords: 2-Diketones; Aromatic 1; o-Phenylenediamine; Quinoxaline; Room temperature; Titanium silicate-1